1991
DOI: 10.1113/jphysiol.1991.sp018480
|View full text |Cite
|
Sign up to set email alerts
|

The effect of static exercise on renal sympathetic nerve activity in conscious cats.

Abstract: SUMMARY1. Renal sympathetic nerve activity (RNA), heart rate (HR), arterial blood pressure (AP), and force development were measured simultaneously during voluntary static (isometric) exercise performed by conscious cats. The cats were operantly trained to press a bar with one forelimb. When the force applied to the bar exceeded a predetermined value (threshold), a sound was emitted by a buzzer for audio-feedback. If the cat continued to produce the appropriate force for a period of 26-55 s, food was given as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
3

Year Published

1996
1996
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 15 publications
7
53
3
Order By: Relevance
“…The peak force during static exercise in conscious cats corresponded to ϳ17% of their body weight. Since the maximally developed force was nearly 1.0 kg in the present and previous studies (5,9,24,26), the cats seemed to produce ϳ60% of the maximal voluntary force at the most, and the intensity of static exercise appeared mild or moderate. Thus the exercise intensity might be insufficient to initiate the muscle mechanoreflex, the contribution of which remains to be studied with a higher intensity of static exercise.…”
Section: Limitationssupporting
confidence: 56%
See 3 more Smart Citations
“…The peak force during static exercise in conscious cats corresponded to ϳ17% of their body weight. Since the maximally developed force was nearly 1.0 kg in the present and previous studies (5,9,24,26), the cats seemed to produce ϳ60% of the maximal voluntary force at the most, and the intensity of static exercise appeared mild or moderate. Thus the exercise intensity might be insufficient to initiate the muscle mechanoreflex, the contribution of which remains to be studied with a higher intensity of static exercise.…”
Section: Limitationssupporting
confidence: 56%
“…Although these limitations must be taken into account, the present finding that gadolinium did not at all alter the time course and magnitude of the cardiovascular responses at the onset of voluntary static exercise in conscious cats suggests a role of central command in producing the initial cardiovascular adaptation at least in the presence of gadolinium. The central command hypothesis is supported by previous findings from Matsukawa and colleagues (24,25,43) demonstrating that cardiac and renal sympathetic efferent nerve activities start to increase immediately before or at the onset of static and dynamic exercise, which in turn contributes to tachycardia and pressor response in several seconds. The rapid sympathetic nerve responses are hardly explained by the muscle mechanoreflex.…”
Section: Central Command But Not the Muscle Mechanoreflex Is Responmentioning
confidence: 62%
See 2 more Smart Citations
“…In animals, the mechanoreflex has been shown to modulate the renal vascular bed. 22,23 For example, in chloralose-anesthetized cats, mechanical stimulation of the triceps surae muscle produces an immediate reflex increase in efferent renal sympathetic nerve activity. 22 In normal humans, we have reported that central command and/or mechanoreceptors help mediate reflex renal vasoconstriction during static handgrip exercise.…”
Section: Middlekauff Et Al Exercise Renal Vasoconstriction In Heart Fmentioning
confidence: 99%